2008
DOI: 10.1002/mnfr.200700385
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cytokine production by plant sterols in stimulated human Jurkat T cells

Abstract: The plant sterols campesterol, beta-sitosterol and beta-sitostanol were investigated for potential immunomodulatory effects in Jurkat T cells. Treatments involved supplementing cells with or without concanavalin A (ConA) or phorbol-12-myristate-13-acetate plus ionomycin (PMA+IoM) in the presence or absence of increasing concentrations (10-100 microM) of each plant sterol for 24 h. None of the plant sterols significantly affected mitogen-stimulated IL-4, IL-10 or IFN-gamma production. However, campesterol, beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…For b-sitosterol, studies have demonstrated important anti-inflammatory activity not only by inhibiting IL-12 from human Jukart T cells stimulated by concanavalin (ConA) or by phorbol-12-myristate-13-acetate plus ionomycin (PMA + IoM) (Aherne & O'Brien, 2008), but also by decreasing the eosinophil influx, mucus secretion, and IL-4/ IL-5 expression in a murine model of asthma induced by ovalbumin (Yuk et al, 2007), and the ear oedema induced by acetone in mice (Mavar-Manga et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For b-sitosterol, studies have demonstrated important anti-inflammatory activity not only by inhibiting IL-12 from human Jukart T cells stimulated by concanavalin (ConA) or by phorbol-12-myristate-13-acetate plus ionomycin (PMA + IoM) (Aherne & O'Brien, 2008), but also by decreasing the eosinophil influx, mucus secretion, and IL-4/ IL-5 expression in a murine model of asthma induced by ovalbumin (Yuk et al, 2007), and the ear oedema induced by acetone in mice (Mavar-Manga et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the fact that we planned to assess the effects of the casein hydrolysates on Concanavalin A (ConA)-stimulated interleukin-2 (IL-2) and interleukin-10 (IL-10) production, we chose the Jurkat T cell model for our study. Human Jurkat T cells possess membrane markers that resemble normal lymphocytes and have long served as a useful model for different immunological and other bioactivity studies (Aherne and O'Brien, 2008;Konicova et al, 1992;Luongo et al, 2003;Tanaka et al, 2005;Verlengia et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…The effects of casein hydrolysates on ConA-stimulated IL-2 and interleukin-10 (IL-10) production in these cells was also examined. Human Jurkat T cells were selected as they possess membrane markers that resemble normal lymphocytes and have previously been employed as a useful model for immunological and bioactivity studies (Aherne & O'Brien, 2008;Koníková, Babusíková, Kusenda, & Glasová, 1992;Luongo, Bergamo, & Rossi, 2003;Tanaka, Akaishi, Hosaka, Okamura, & Kubohara, 2005;Verlengia et al, 2004). The activity of the hydrolysates was compared with that of intact/unhydrolysed sodium caseinate (NaCN).…”
Section: Introductionmentioning
confidence: 99%